Clinical Results of Arteriovenous Fistulas Constructed Using Autologous Vessels in End-Stage Renal Disease Patients on Hemodialysis - Kim, Ki Tae (Korean J Thorac Cardiovasc Surg, 2018)
BACKGROUND: For hemodialysis patients with end-stage renal disease (ESRD), it is important to construct an efficient vascular access with a superior patency rate. This study investigated the factors influencing the efficiency of arteriovenous fistulas (AVFs) constructed using an autologous vessel and evaluated the necessity of ultrasonography as a preoperative tool for AVF construction. METHODS: A retrospective analysis was performed of 250 patients in whom an AVF was constructed using an autologous vessel due to ESRD at our institution from January 2009 to April 2016. RESULTS: The 1-, 3-, and 5-year patency rates for all subjects were 87.6%, 85.6%, and 84.4%, respectively. The patients who underwent a preoperative evaluation of their vessels via ultrasonography had better patency rates than those who did not. Superior patency rates were found in patients under 65 years of age or with an anastomotic vein diameter of 3 mm or more. The 1-year patency rate and the diameter of the anastomotic vein showed a positive relationship. CONCLUSION: Ultrasonography is strongly recommended for AVF construction, and efforts should be made to increase the patency rate in patients over 65. Superior clinical results can be expected when an AVF is made using an autologous vessel with an anastomotic vein diameter of at least 3 mm.